UPAYA MENINGKATKAN KEMAMPUAN DALAM MENENTUKAN KKM MELALUI PENDAMPINGAN BERKELANJUTAN TERHADAP GURU SD NEGERI 1 KARANGMANGU - Juariah, Yayah (Jurnal Sains Indonesia, 2022)
This research is entitled: "Efforts to Improve Ability in Determining KKM Through Continuous Assistance to Teachers of SD Negeri 1 Karangmangu". The purpose of this study is to improve the ability of teachers to determine KKM through continuous assistance to teachers of SD Negeri 1 Krangmangu, Kramatmulya District, Kuningan Regency, for the 2021/2022 academic year. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of the action research that before the school action research was conducted which achieved an average score of 51.1 or low qualifications, after the first cycle research the teacher's ability level in determining the minimum completeness criteria for the first cycle of school action research reached an average score of 68.59 and then in the second cycle it increased again to 73.8 with high qualifications. Furthermore, the researcher recommends: (1) Principals who have the same difficulty can apply Continuous Mentoring to improve the ability to Determine Minimum Completeness Criteria for Guided Teachers. (2) In order to get maximum results, it is possible to apply individual continuous mentoring intensively and sustainablyt